Participatory Design: An East African Take - Awori, Kagonya; Ssozi, Fiona Catherine; Baguma, Rehema (Participatory Design Conference, 2022)
The East Africa Participatory Design Conference (PDC) place seeks to catalyse engagement and learning between global PDC communities and East Africa. While there has been significant work in participatory design in Africa, much of it remains invisible to international fora, and vice versa. Moreover, much of the ways by which research and innovation in Design is articulated in Africa, differs from how it is at top tier academic venues, further marginalising participation and contribution from African geographies. The East Africa PDC place attempts to tackle these by 1) engaging academics and industry practitioners in Africa in defining and showcasing participatory design work in the region (both East Africa in particular and Africa in general), and 2) making visible to the East Africa community research from PDC that is relevant or interesting to the continent.